2017
DOI: 10.1002/1873-3468.12768
|View full text |Cite|
|
Sign up to set email alerts
|

An inhibitory epitope of human Toll‐like receptor 4 resides on leucine‐rich repeat 13 and is recognized by a monoclonal antibody

Abstract: Lipopolysaccharide (LPS)-induced activation of Toll-like receptor 4 (TLR4) elicits the innate immune response and can trigger septic shock if excessive. Two antibodies (HT4 and HT52) inhibit LPS-induced human TLR4 activation via novel LPS binding-independent mechanisms. The HT52 epitope resides on leucine-rich repeat 2 (LRR2) and is a feature of many inhibitory antibodies; antigen specificity of HT4 does not reside in LRR2. Here, we identified an HT4 epitope on LRR13 located close to the TLR4 dimerization inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…43 Data were analysed using FlowJo software (Tree Star, Ashland, OR). 43 Data were analysed using FlowJo software (Tree Star, Ashland, OR).…”
Section: Cell Staining and Flow Cytometrymentioning
confidence: 99%
“…43 Data were analysed using FlowJo software (Tree Star, Ashland, OR). 43 Data were analysed using FlowJo software (Tree Star, Ashland, OR).…”
Section: Cell Staining and Flow Cytometrymentioning
confidence: 99%
“…The TLR4-MD2 dimerization occurs to initiate a downstream signaling cascade (60). The LPS induction enhances macrophage activation markers like CD14, MHC-II and CD86 expressions and results in the internalization of cell surface TLR4 (51,52,(61)(62)(63)(64). As reported previously, activation of TLR4 leads to phosphorylation of NF-kB (55) and thus has a direct correlation with inflammation (58, 59).…”
Section: Discussionmentioning
confidence: 73%
“…Hu 15C1 is a potent anti-TLR4 mAb, which, owing to its efficacy, has reached clinical trials and is being evaluated in RA patients [ 25 ]. The epitope of mAb Hu 15C1 has been mapped by alanine mutagenesis and has been found to be located in the ectodomain of TLR4 near the dimerization interface [ 27 ]. This epitope has also been investigated in another study [ 26 ], in which a new derivative antibody, C2E3, was designed.…”
Section: Resultsmentioning
confidence: 99%
“…These observed impacts including steric clashes, hydrogen bond network disruption or abrogation of antibody binding, can lead to gain or loss in function of the receptor [ 33 , 34 ]. Moreover, Tsukamoto et al, assessed the functional role of TLR4 activation by a dual-luciferase NF-κB reporter assay, and demonstrated that the overexpression of TLR4 wt induced NF-κB activation was reduced upon transfection of the mutated plasmid in which LLR13 residues (TLR4 residing epitope) were mutated [ 27 ]. From these studies, we can assume that the mutation-driven structure change makes the antibody unable to recognize the epitope, and these residues play a functional role in TLR4 activation as they are essential for dimerization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation